False positive ketamine urine immunoassay screen result induced by quetiapine: A case report - Chun-Hao Liu (Journal of the Formosan Medical Association, 2017)
Ketamine immunoassay urine drug screen (UDS) is commonly used in Taiwan. However, there was limited report about possible drug which may cause false positive results in ketamine screen test. We report two cases who used quetiapine showed positive in ketamine urine immunoassay screen initially, and found to be false positive in confirmation test. Clinicians should be aware of the false positive result of ketamine UDS caused by currently used medication.